Identity Development in Adulthood: Introduction. Issue 1 (2nd January 2016) - Fadjukoff, Päivi; Kroger, Jane
ABSTRACT: In line with Erikson's suggestions, increasing empirical evidence substantiates that considerable identity development takes place over the course of adulthood. What then does identity development during adulthood entail? The key findings of adult identity formation from four culturally different countries, and the challenges of analyzing the complex concept of identity are discussed. Although a wide array of identity measures are available, they have not been sufficiently validated for use with middle-aged or older adults. Additionally, different measures may yield results that are not comparable across studies. More studies are needed on adult identity development in populations representing different ethnicities and living in different cultural environments.